1997
DOI: 10.1002/1521-396x(199711)164:1<235::aid-pssa235>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Domain Formation and Multistability in Semiconductor Multiple Quantum Wells in the Presence of THz Radiation

Abstract: We propose a self‐consistent microscopic model of vertical sequential tunneling through multiple quantum wells in the presence of THz radiation. The model considers the Coulomb interaction in a mean field approximation. We analyze the current density through a double quantum well and a superlattice and study the formation of electric field domains in the presence of THz radiation and the appearance of new multistability regions, both caused by the combined effect of the strong nonlinearity coming from the Coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a more strongly coupled SL under terahertz radiation, the same authors observed dynamic localization, absolute negative conductance and stimulated, multiphonon emission [274]. Subsequently, a theoretical investigation by Aguado and Platero [275,276] using a self-consistent microscopic model of sequential tunnelling through multiple quantum wells in the presence of terahertz fields showed how the EFDs can be supported by virtual photonic sidebands due to multiple photon emission and absorption. Very recently, the same authors [17] published a detailed review of photon-assisted transport in semiconductor nanostructures.…”
Section: Photon-assisted Domain Formationmentioning
confidence: 92%
“…In a more strongly coupled SL under terahertz radiation, the same authors observed dynamic localization, absolute negative conductance and stimulated, multiphonon emission [274]. Subsequently, a theoretical investigation by Aguado and Platero [275,276] using a self-consistent microscopic model of sequential tunnelling through multiple quantum wells in the presence of terahertz fields showed how the EFDs can be supported by virtual photonic sidebands due to multiple photon emission and absorption. Very recently, the same authors [17] published a detailed review of photon-assisted transport in semiconductor nanostructures.…”
Section: Photon-assisted Domain Formationmentioning
confidence: 92%